Adapting of Spectrophotometric Assay of Paraoxonase Activity with 4-Nitrophenylacetate for Murine Plasma and Liver - Vatashchuk , Myroslava; Hurza , Viktoria; Bayliak , Maria (Journal of Vasyl Stefanyk Precarpathian National University, 2023)
Paraoxonase 1 (PON1) is the most studied enzyme of the paraoxonase family, which are mammalian enzymes with aryldialkylphosphatase activity. Paraoxonase 1 was first described in the 1940s as an enzyme found in mammalian tissues capable of hydrolyzing organophosphate pesticides. However, recent studies have shown that PON1 also plays a protective role in diseases related to inflammation and oxidative stress, and exhibits anti-inflammatory, antioxidant, anti-atherogenic, and detoxifying properties. In particular, an important function for PON1 is to protect against vascular diseases by metabolizing oxidized lipids in blood lipoprotein complexes. Some studies show that reduced PON1 activity is associated with the risk of developing cardiovascular disease, as well as obesity, metabolic syndrome, and cancer. Thus, PON activity can be an important biomarker in the diagnosis of the above-mentioned diseases. Paraoxonase 1 is synthesized in the liver, then released into the bloodstream and is found mainly in high-density lipoproteins. Because PON1 has broad substrate specificity, different activities of PON1 can be assessed. In this study, we optimized the conditions for the spectrophotometric determination of paraoxоnase activity in the blood and liver of mice. The PON1 arylesterase activity protocol was adapted using nitrophenylacetate as a substrate. A concentration of 3.2 mmol/l nitrophenylacetate was chosen for the analysis of PON in mouse tissues. Specific PON activity was different in mouse tissues – 210±17 mU/mg in blood plasma and 66.5±8.5 mU/mg in liver. Therefore, the supernatant volume recommended for PON determination is 5 µl for plasma and 10 µl for liver homogenate in a total reaction mixture of 1.25 ml.